Improving Speaking through Role Plays and Dramatization - Cárdenas R. Diana; Robayo Ruiz María Deisy (Profile: Issues in Teachers' Professional Development)
Frequently, in our English classes, we observe our students working on some tasks and some questions come to our
minds: Are we using good procedures to teach English?. Are they effective ways to learn English? and in general: What can we do in order to improve English learning?. These reflections belong to a wide field of research. We concentrated on one
of the skills that we consider basic to develop the overall improvement of English as a second language: speaking. After some pedagogical reflections concerning oral activities in the
classroom, we chose some role-plays and dramatizations to determine their impact on students´ oral production and the effect they may have on students´ learning processes.